Ozone treatment promotes physicochemical properties and antioxidant capacity of fresh-cut red pitaya based on phenolic metabolism - Li, Chen; Wang, Shan; Wang, Jiayi; Wu, Zhaohui; Xu, Yaping; Wu, Zhaoxia (Frontiers in Nutrition, 2022)
Pitaya is an important fresh-cut product in the global fruit market. The health benefits of fresh-cut red pitaya fruit are attributed to its unique phenolic content and other antioxidants, but the fruit is highly susceptible to spoilage which causes a decline in nutritional quality. In this study, we monitored changes in quality and phenolic compounds of pitaya fruit treated with gaseous ozone during storage at 8 ± 2 ℃ for 4 days. Compared with the control group, ozone treatment was an effective strategy for preserving quality by controlling the growth of microorganisms, preventing weight loss and softening, and improving the content of soluble solids and titratable acids. The results showed that ozone induced the accumulation of phenolic compounds while maintaining the quality. The content of phenolic compounds in fresh-cut pitaya was positively correlated with antioxidant activity. Ultra-performance liquid chromatography-electrospray tandem mass spectrometry was used to fingerprint the phenolic metabolites and metabolomic analysis identified 26 phenolic compounds. The majority of these were phenylpropanoids, and the key metabolic pathways were phenylpropane metabolism and flavonoid synthesis. This study illustrated the mechanism by which of ozone prolongs the shelf life of fresh-cut pitaya fruit and validated ozone as a valuable phenolic inducer and regulator of antioxidant activity, positively influencing the potential health benefits of fresh-cut products.